Consider the following ‘proof’ where for convenience we have numbered each

step.

1. Clearly ( 1)

2

= 1, and so

2. upon taking logarithms we have that ln( 1)

3. Using one of the logarithm rules we have that 2 ln( 1) = 0,

4. or upon division by 2, that ln( 1) = 0.

5. Therefore el

n( 1)

= e0

,

6. which simplifies to 1 = 1.

The conclusion of the ‘proof’ is clearly false, so explain exactly at what

step(s) things went wrong.

So basically I got for the answer: log(-1)(1)=2

I just want to know if my answer is right. I would really appreciate some helps thanks!